Responses of young cucumber plants to a diurnal temperature drop at different times of day and night - Tatjana G. SHIBAEVA; Elena G. SHERUDILO; Elena N. IKKONEN; Alexander F. TITOV (Acta Agriculturae Slovenica)
In greenhouse production of a number of vegetable and ornamental plant species, a short diurnal temperature drop in the end of the night or in the morning is commonly used to reduce stem elongation as an alternative to chemical growth retardants. Experiments were carried out to quantify the effects of a temperature drop at different times of the day and night on growth and photosynthetic activity of young cucumber plants. During 6 days plants were exposed daily to a temperature of 10 °C for 2 h at the beginning, in the middle and at the end of the night and day periods. The results have shown that plant response to drop may be qualitatively different in the light and darkness. While strongest effects of drop are observed when it is given in the daytime, for practical application in greenhouses it is more appropriate to reduce temperature at night. However, it may not be strictly necessary for cucumber seedlings to apply drop at the end of the night as it was stated in the literature. Thus, our results may cast doubt on the following statements: (a) temperature drops are not effective when delivered at other times of the day or night (except before sunrise), (b) optimal time for drop effects depends on the daily dynamics of stem and petiole elongation rate. It is rather drop itself is capable of modifying the dynamics of plant growth in the daily cycle.